Prophetic Da’wah and Community Development: Muhammad Abdullah Muchtar’s Empowerment Model at SPMAA - Ibrahim Hafidhson Muchtar (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2026)
This study examines how Muhammad Abdullah Muchtar’s prophetic thought shapes the design, implementation, and scalability of a community development-based da’wah model at Sumber Pendidikan Mental Agama Allah (SPMAA). The study seeks to explain how the principle of khidmah lil-ummah (service to humanity) is institutionalized into educational, social welfare, and environmental programs and how these programs align with community development principles. This research employed a qualitative biographical study design grounded in an interpretivist paradigm. Data were collected from January to March 2026 through documentary analysis of SPMAA’s organizational guidelines, institutional publications, program documents, and founder-related texts. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, encompassing data condensation, data display, and conclusion drawing. The findings were interpreted through the lens of Ife and Tesoriero’s community development framework, particularly the dimensions of participation, empowerment, and sustainability. The findings reveal that khidmah lil-ummah functions as the normative architecture of SPMAA’s institutional design, shaping program priorities, organizational culture, and community engagement strategies. The education domain demonstrates the strongest alignment with community development principles through its vertically integrated educational pathway, generating long-term empowerment and sustainability outcomes. The social welfare domain exhibits strong participation and social inclusion but only moderate empowerment due to its emphasis on rehabilitation and assistance. The environmental domain shows the weakest alignment, reflecting a gap between strong theological commitment and limited programmatic infrastructure. Furthermore, SPMAA’s expansion across approximately 117 locations and 3,000 members indicates that prophetic-value-driven institutions can achieve geographical scalability without losing normative coherence. This study introduces a Founder-Centered Prophetic Da’wah Framework, demonstrating how a founder’s ethical vision becomes institutionalized into a sustainable community empowerment model. The study advances Islamic da’wah scholarship by moving beyond program-oriented analysis toward a founder-centered perspective and enriches community development theory by demonstrating the structural convergence between Islamic prophetic ethics and community development principles.